2014
DOI: 10.7314/apjcp.2014.15.8.3801
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Hematologic Parameters in Patients with Metastatic Renal Cell Carcinoma Using Tyrosine Kinase Inhibitors

Abstract: This study showed that increased pretreatment NLR is an independent prognostic factor for patients with metastatic RCC using tyrosine kinase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Nakano et al (9) investigated the association between NLR and survival outcome in preoperative local and locally advanced breast cancer and concluded that it may be an independent prognostic factor for disease-free survival and breast cancer-specific survival in patients with breast cancer. It has also been demonstrated that increased pretreatment NLR is an independent prognostic factor in patients with metastatic renal cell carcinoma who received tyrosine kinase inhibitors (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nakano et al (9) investigated the association between NLR and survival outcome in preoperative local and locally advanced breast cancer and concluded that it may be an independent prognostic factor for disease-free survival and breast cancer-specific survival in patients with breast cancer. It has also been demonstrated that increased pretreatment NLR is an independent prognostic factor in patients with metastatic renal cell carcinoma who received tyrosine kinase inhibitors (14).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophilia may inhibit the immune system by suppressing lymphocytes, activated T cells and natural killer cells (3,17). The prognostic role of the NLR has been evaluated in >60 studies on a number of solid tumors (7)(8)(9)(10)(11)(12)(13)(14)16,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the morbidity and cost-effectiveness of this drug is also a problematic issue. The objective of this study was to evaluate the efficiency of bevacizumab in the first line treatment of mCRC patients when added to standard combination chemotherapy and to analyze the predictive role of clinicopathologic and biochemical parameters, including the neutrophil/lymphocyte ratio, shown to be relevant as a diagnostic or prognostic factors for many cancers (Unal et al, 2013;Zheng 2013;Cihan et al, 2014;Gunduz et al, 2014;Kacan et al, 2014;Kemal et al, 2014;Ozdemir et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…C-reactive protein, neutrophil or platelet count which correlates with systemic inflammation has been shown as a prognostic factor in different cancer types. Various studies have shown that high NLR is a poor prognostic factor such as in pancreatic, colorectal, lung, breast cancers (6)(7)(8)(9)). An increased neutrophillymphocyte ratio (NLR) has been proposed as a marker to predict the prognosis of RCC patients and many studies found preoperative NLR as a poor prognostic marker in RCC (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%